A dual-channel chemodosimetric sensor for discrimination between hypochlorite and nerve-agent mimic DCP: application on human breast cancer cells. Issue 23 (1st June 2022) - Mandal, Moumi; Guria, Uday Narayan; Halder, Satyajit; Karak, Anirban; Banik, Dipanjan; Jana, Kuladip; Kar, Arik; Mahapatra, Ajit Kumar
Abstract : A styryl bridge containing triphenylamine-thioimidazole hydrazine-based fluorescent dye has been designed to selectively sense nerve-agent mimic DCP and toxic OCl- anion. It also used for the detection of human breast cancer cell. Abstract : A styryl bridge containing a triphenylamine–thioimidazole hydrazine-based dual-analyte-responsive fluorescent sensor was designed and synthesized for the detection of the nerve gas simulant diethyl chlorophosphate (DCP) and hypochlorite (OCl − ) for the first time. Hypochlorite induces oxidative intramolecular cyclization to give a triazole structure, which exhibited blue fluorescence with excellent selectivity and a low detection limit (8.05 × 10 −7 M) in solution. Conversely, the probe forms a phosphorylated intermediate with diethyl chlorophosphate, which undergoes further hydrolyzation and presents green fluorescence in a ratiometric mode with a low detection limit (3.56 × 10 −8 M). Additionally, the as-designed sensor was utilized to construct a portable kit for real-time monitoring of DCP in a discriminatory, simple and safe manner. Lastly, the probe was also productively employed for in situ imaging of OCl − and DCP in the living cell.